2015
DOI: 10.1111/pedi.12298
|View full text |Cite
|
Sign up to set email alerts
|

Association between IgE-mediated allergies and diabetes mellitus type 1 in children and adolescents

Abstract: Our results suggest that T1DM is associated with a higher risk of a self-reported presence of IgE-mediated allergies and that the Th1/Th2-hypothesis may be an oversimplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
2
15
0
4
Order By: Relevance
“…9 In 2015, Klamt et al designed a prospective case-control study to investigate the association between the prevalence of T1DM and IgE-mediated allergies. 10 The results implied that T1DM is associated with an increased risk of self-reported IgE-mediated allergies. However, in a large prospective study involving 14 849 individuals from five study populations, including 834 cases with autoimmune disease, 11 Skaaby et al did not find a statistically significant association between atopy and the development of any autoimmune disease, including T1DM.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…9 In 2015, Klamt et al designed a prospective case-control study to investigate the association between the prevalence of T1DM and IgE-mediated allergies. 10 The results implied that T1DM is associated with an increased risk of self-reported IgE-mediated allergies. However, in a large prospective study involving 14 849 individuals from five study populations, including 834 cases with autoimmune disease, 11 Skaaby et al did not find a statistically significant association between atopy and the development of any autoimmune disease, including T1DM.…”
Section: Discussionmentioning
confidence: 90%
“…However, the results of recent studies investigating the association between the two diseases are controversial. [7][8][9][10][11] In 2011, Thomsen et al examined the association between T1DM and atopic diseases in a twin population registered in the Danish Twin Registry. 7 They found that the age-adjusted and sex-adjusted risk of atopic dermatitis was lower in patients with T1DM than in non-diabetics, whereas asthma and allergic rhinoconjunctivitis were non-significantly associated with T1DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Это будет означать, что развитие IgE-опосредованной аллергии (Th2-путь) будет понижать риск развития СД1 [16]. Известно, что Th1-эффекторы CD4 + играют су-щественную роль в противовирусном иммуните-те [14].…”
Section: телесманич нр и др Medical Immunology (Russia)/meditsinskunclassified
“…В последнее время практически сформировалось воззрение, что усиление IgE-поликлонального ответа и противовоспалительных цитокинов считают маркером экспансии Th2 и развитием иммунной системы по аллергическому типу, что понижает риск развития сахарного диабета 1 типа (СД1). И наоборот, пациенты, болеющие СД1, мало подвержены аллергии [14]. Существует мне-ние, что у лиц с разными группами крови (АВ0) могут быть различия в индивидуальном уровне адаптивной реакции организма.…”
Section: Introductionunclassified